Effect of streptozotocin-induced diabetes on motoneurons and muscle spindles in rats. (February 2017) - Muramatsu, Ken; Niwa, Masatoshi; Tamaki, Toru; Ikutomo, Masako; Masu, Yujiro; Hasegawa, Tatsuya; Shimo, Satoshi; Sasaki, Sei-Ichi
Highlights: The number of alpha motoneurons is decreased in early stage of type 1 diabetes. The number of gamma motoneurons is decreased in later stage of type 1 diabetes. Muscle spindles showed denervation atrophy in a diabetic model. Abstract: This study examined the alterations in the number and size of motoneurons innervating the medial gastrocnemius (MG) and biceps femoris (BF) motor nuclei in diabetic rats (12 or 22 weeks after injection of streptozotocin) and age-matched controls using retrograde labeling technique. Additionally, morphological alterations of muscle spindles in BF and MG muscles were tested. Significantly fewer labeled MG motoneurons were found in 12- and 22-week diabetic rats as compared with age-matched control animals. In contrast, the number of BF motoneurons was preserved in each group. Compared to control animals, the ratio of larger motoneurons of MG and BF muscle were decreased at 12 weeks, and smaller MG motoneurons were drastically decreased at 22 weeks. Moreover, MG muscle spindle showed reduction of its number and increase of intrafusal muscle fibers; however, BF muscle spindles showed little or no difference from control animals. We conclude that there is an early loss of alpha motoneurons for both MG and BF muscles followed by a later loss of gamma motoneurons in MG muscle in diabetic animals. Moreover, loss of gamma motoneuron might induce atrophy of MG muscle spindles.